SEXO Y OTRAS ESTRATEGIAS DE CAMPAÑA. EL CASO DE LAS ELECCIONES AL PARLAMENT DE CATALUÑA 2010 - Dra. Palma PEÑA JIMÉNEZ (Fonseca, Journal of Communication, 2023)
In the Catalan elections of 2010 spots had a much wider presence than any other propaganda election tool